2022
DOI: 10.1002/anie.202202972
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Catalyzed Asymmetric Formal Hydroamination of Allylic Alcohols: A Remarkable Macrocyclic Ligand Effect

Abstract: A unique family of chiral peraza N 6 -macrocyclic ligands, which are conformationally rigid and have a tunable saddle-shaped cavity, is described. Utilizing their manganese(I) complexes, the first example of earth-abundant transition metal-catalyzed asymmetric formal anti-Markovnikov hydroamination of allylic alcohols was realized, providing a practical access to synthetically important chiral γ-amino alcohols in excellent yields and enantioselectivities (up to 99 % yield and 98 % ee). The single-crystal struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 109 publications
1
20
0
Order By: Relevance
“…The presence of functional groups and the possibility of adaptation of different stable conformations has made the macrocycles 1 – 9 good candidates for being molecular building blocks (tectons) in molecular tectonics. This part of the study corresponds well with an increasing interest, observed in recent years, in applications of chiral, periodical, and (formally) symmetrical polyaza macrocycles in various aspects of material chemistry and crystal engineering. In partiuclar, the manipulation of the shape complementarity between macrocyclic molecules would give a premise to the formation of various supramolecular architectures stabilized by the guest molecules.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The presence of functional groups and the possibility of adaptation of different stable conformations has made the macrocycles 1 – 9 good candidates for being molecular building blocks (tectons) in molecular tectonics. This part of the study corresponds well with an increasing interest, observed in recent years, in applications of chiral, periodical, and (formally) symmetrical polyaza macrocycles in various aspects of material chemistry and crystal engineering. In partiuclar, the manipulation of the shape complementarity between macrocyclic molecules would give a premise to the formation of various supramolecular architectures stabilized by the guest molecules.…”
Section: Resultssupporting
confidence: 71%
“…This part of the study corresponds well with an increasing interest, observed in recent years, in applications of chiral, periodical, and (formally) symmetrical polyaza macrocycles in various aspects of material chemistry and crystal engineering. 86 91 In partiuclar, the manipulation of the shape complementarity between macrocyclic molecules would give a premise to the formation of various supramolecular architectures stabilized by the guest molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, Chen, Fan, and co-workers reported the use of a chiral peraza- N 6 -macrocycle and [Mn(CO) 5 Br] for the in-situ formation of a complex capable of catalyzing the asymmetric hydroamination of allylic alcohols with excellent regio- and stereoselectivities ( Figure 16 , Mn-29 ). 99 Interestingly, this system was highly influenced by the added base and the structure of the macrocycles; for the latter, the main changes were observed in the catalytic activity but not in the stereoselectivity. In stark contrast, the use of open-chain ligands (not macrocyclic) led to null conversions.…”
Section: Hydrofunctionalization Of Unsaturated C–c Bondsmentioning
confidence: 99%
“…When racemic secondary allylic alcohols were employed, the enantio-determining control would present at the third step. Most recently, the Wang, [15] Xing, [16] and Fan [17] groups independently demonstrated this process by employing a single chiral ruthenium or cobalt complex as the borrowing-hydrogen catalyst. In contrast, a more complicated and powerful chirality control mode using two distinct chiral catalysts to induce the sequential asymmetric events of the second and third step, namely one-pot stereodivergent synthesis via relay catalysis, has not yet been investigated.…”
mentioning
confidence: 99%
“…Notably, besides phenyl and naphthyl substituted allylic alcohols, heteroaromatic ringsubstituted allylic alcohols 1 r-1 u proved to be viable reactants, affording the desired products 3 r-3 u in satisfactory yield (43 %-90 %) with acceptable diastereoselectivity (8 : 1-11 : 1 dr) and top level of enantioselectivity (99 % ee) (entries [18][19][20][21]. In order to further explore the compatibility of this relay catalytic system, we turned our attention to the more challenging alkyl-substituted secondary allylic alcohols 1 v and 1 w. [15][16][17] When methyl group substituted allylic alcohol 1 v was subjected to the slightly modified reaction conditions, the corresponding reaction could proceed smoothly, furnishing the desired product 3 v in a high yield (82 %) with an excellent level of ee value (95 %) albeit low diastereoselectivity [23] (1.3 : 1 dr) (entry 22). Replacing methyl group with sterically hindered cyclohexyl group, to our delight, a good yield (65 %) with excellent enantiomer excess (99 % ee) and high diastereoselectivity (10 : 1 dr) could be obtained (entry 23).…”
mentioning
confidence: 99%